PEMURNIAN SILIKA AMORF HASIL DARI PEMUNGUTAN LUMPUR PANAS BUMI DIENG : METODE PENCUCIAN KERING - , RENUNG RENINGTYAS ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Geothermal power plant in Dieng, Indonesia, always produces sludge as a side product which mainly contains amorphous silica with a purity of about 55%. The waste is one of promising sources as a raw material for producing high grade amorphous silica. Preliminary study in recovery of silica from Diengâs geothermal sludge through sol-gel extraction in sodium hydroxide solution had been performed and 80% purity of amorphous silica was obtained. The impurities were mainly sodium and volatile matters. In the presence work, two washing methods to remove sodium were applied namely wet-gel and dried gel washing methods. The objectives of this research were to study dried gel washing methods for increasing the purity of amorphous silica product and to propose a mathematical model for silica gel drying. The main advantage of using dried gel washing method was that the amount of distilled water used to produce silica with Â±7% sodium in purity was about 40% of water used for wet-gel washing method. The removal of sodium using dried gel washing method was much easier and faster compared with that of wet-gel washing method. Sodium content in silica was determined using atomic absorption spectroscopy (AAS) and functional group using fourier transform infrared spectroscopy (FTIR). Drying process was investigated by thermal gravimetric differential thermal analysis (TG-DTA) through nonisothermal experiments at different heating rates. Two simultaneous processes, namely mass transfer of physically bounded water from gel to air and first order reaction of chemically bounded water to become physically bounded water, were included in the silica gel drying model. From FTIR intrepetation, the chemically bounded water was showed by the presence of silanol groups. According to Friedman isoconversional methods, the apparent activation energy of chemically bounded water reaction is in the range of 50-170 kJ/mole.